PZT actuators as on-board instruments to reduce vibrations and strains in submerged structures. Issue 1 (1st September 2022) - Sánchez-Botello, X; De La Torre, O; Roig, R; Costa-Castelló, R; Escaler, X
Abstract: This paper presents the design and evaluation of an active control system to reduce vibrations and strains of submerged structures. For that, a metallic disk mounted in a test rig has been equipped with on-board waterproof strain gauges and accelerometers, to measure its structural response, and with an on-board PZT actuator patch, to provide the required control force. This control force is computed in real-time by an optimal algorithm that determines the exact voltage to be supplied to the PZT patch in order to mitigate any increase of vibrations and/or strains detected by the sensors. In order to capture the dynamics of the structure when it is excited both in air and submerged in water, a plant model has been identified from the Frequency Response Functions (FRFs) obtained experimentally from the measured vibrations and numerically from simulated strains. With these plant models, two different control techniques based on a Linear Quadratic Gaussian (LQG) controller and on an H ∞ controller have been implemented and simulated under different types of excitations. The obtained results are satisfactory and support the need to continue the research to validate them experimentally.